Notch signaling differentially regulates the cell fate of early endocrine precursor cells and their maturing descendants in the mouse pancreas and intestine - Li, H. Joyce (2012)
Notch signaling inhibits differentiation of endocrine cells in the pancreas and intestine. In a number of cases, the observed inhibition occurred with Notch activation in multipotential cells, prior to the initiation of endocrine differentiation. It has not been established how direct activation of Notch in endocrine precursor cells affects their subsequent cell fate. Using conditional activation of Notch in cells expressing Neurogenin3 or NeuroD1, we examined the effects of Notch in both organs, on cell fate of early endocrine precursors and maturing endocrine-restricted cells respectively. Notch did not preclude the differentiation of a limited number of endocrine cells in either organ when activated in Ngn3(+) precursor cells. In addition, in the pancreas most Ngn3(+) cells adopted a duct but not acinar cell fate; whereas in intestinal Ngn3(+) cells, Notch favored enterocyte and goblet cell fates, while selecting against endocrine and Paneth cell differentiation. A small fraction of NeuroD1(+) cells in the pancreas retain plasticity to respond to Notch, giving rise to intraislet ductules as well as cells with no detectable pancreatic lineage markers that appear to have limited ultrastructural features of both endocrine and duct cells. These results suggest that Notch directly regulates cell fate decisions in multipotential early endocrine precursor cells. Some maturing endocrine-restricted NeuroD1(+) cells in the pancreas switch to the duct lineage in response to Notch, indicating previously unappreciated plasticity at such a late stage of endocrine differentiation.